Evaluation of Logistic Performance Index of India in the Indian Postal Services - K.Selvavinayagam; V.Jothi Francina; V.P.Rameshkumaar (International Journal of Engineering and Management Research, 2018)
The importance of efficient logistics for postal growth is widely acknowledged. Literature has shown that better logistics performance is strongly associated with postal expansion, export diversification, ability to attract foreign direct investments, and economic growth. On the other hand, Indian postal services represents a challenge to logistic operations in transporting and storing products. High logistic costs and low quality of services may be considered obstacles to Indian postal services. This research aims to assess India’s Logistics Performance Index (LPI) in relation to its major competitors in Indian postal services. The inter-national postal data was collected from various post offices in few districts like Salem, Namakkal, Erode.Statistical techniques such as cluster analysis and multiple comparison tests of means have been applied to analyze the data. The competitiveness of Indian domestic firms depends crucially on a dynamic and competitive internal logistic environment in order to stand up to other countries. The results also indicate the bureaucracy as a major obstacle to the logistic performance of the country. The dimension Timeliness of India is very close to the High Logistics Performance Group (HLPG) while Customs is very close to the Low Logistics Performance Group (LLPG). Although India has failed in its customs operations, there seems to be more credibility in Indian dealings. The main contribution of this paper is to reveal logistical aspects in which India has shown large inefficiencies. The difference among the logistic performance index also appears to be relevant to governments to address their new public policies and also to highlight the logistic obstacles of the Indian Indian postal services.